Modified port placement and pedicle first approach for laparoscopic concomitant cholecystectomy and splenectomy in children - Pal Kamalesh (Wolters Kluwer Medknow Publications, 2010)
Aim : Laparoscopy is becoming the preferred modality for concomitant cholecystectomy and splenectomy (CAS). Usually, six to seven ports are employed for CAS, and spleen is removed by classical lateral approach or anterior approach. We report here our modified five-port and pedicle first approach for CAS in children to minimize the intraoperative bleeding and maximize the access. Materials and Methods : Twenty-one children underwent laparoscopic CAS with this new approach and their data were recorded prospectively. Following cholecystectomy (with ports 1-4), left side was elevated by 30°. The spleen was lifted by a grasper/fan retractor through port no. 5. The pedicle was dissected and splenic vessels were divided by ligasure (vessels < 8 mm), and for bulkier pedicle, vascular endo-GIA stapler was used. Short gastric and gastrosplenic ligament, lower pole and phrenico-colic attachments and upper pole attachments were dissected by ligasure in that sequence. Spleen was placed in endosac and delivered by digital fracture technique. Occasionally, lower transverse incision was made to deliver a massive spleen. Results : There were 12 males and 9 females with an average age of 8 years. Fourteen had sickle cell disease (SCD) and 7 had SCD and beta thalassemia. All CAS were completed successfully without any complication. Total duration was 160 minutes. Cholecystectomy took an average of 35 minutes. Average blood loss was 140 ml. The mean splenic weight was 900 g and mean length was 20 cm. Duration of hospitalization was 3-4 days. Conclusion : CAS can be successfully performed by five ports. The pedicle first approach is extremely helpful in moderate to massive spleens as it reduces splenic size, vascularity and bleeding from capsular adhesions or inadvertant lacerations.